Michaels dybe spor i dansk folketro, kunst og kirker - Andersen, Christian (Kirkehistoriske Samlinger, 2003)
It has been suggested by Tore Nyberg that the building of churches between 900 and 1100 took place according to a certain plan, with only one church in a certain area, ecclesia baptismalis, used for baptisms. These main churches were most often named after Saint Michael and this article records the 23 different Danish churches with this consecration. The history of the individual churches, it is argued, supports the thesis of these churches being built as central baptismal churches.